Competitiveness Analysis and Growth Path of Jiangsu’s Cruise Industry Development - Jiang, Rui; Zhang, Xiaowei (Journal of Global Economy, Business and Finance, 2025)
As a key economic province in the Yangtze River Delta, Jiangsu holds significant potential for cruise industry development but faces challenges such as intensified regional competition and an incomplete industrial chain. This paper evaluates Jiangsu’s cruise industry competitiveness by analyzing its resource endowments, market demand, policy environment, and technological innovation capabilities, employing a SWOT framework. It proposes four growth paths: differentiated development, industrial chain collaboration, innovation-driven strategies, and internationalization. The study suggests that Jiangsu should focus on integrating “cruise and cultural tourism,” establishing regional coordination mechanisms, and breaking through core technologies to enhance global competitiveness and achieve high-quality development.